Pengembangan Media Pembelajaran Video Interaktif Berbasis Quizizz Sebagai Upaya Edukasi Anti-Bullying di MTSN 1 Kota Bekasi - Khansa Labiibah Hasna; Afifah Nur Zakiah; Elisa Qotrunada; Zhahira Zahratunnisa4 (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Bullying at school is a social problem that has a serious impact, both physically and mentally on students. At MTsN 1 Bekasi City, efforts have been made to prevent bullying through various anti-bullying educational programs, such as introducing the types of bullying, managing emotions, and career preparation. However, innovation is still needed to make anti-bullying educational programs more attractive to students. One potential innovation is the development of interactive educational video-based learning media to increase students' understanding of bullying and encourage student’s active participation in creating a safe and comfortable school environment. This research uses the Research and Development (R&D) method with the ADDIE development model, which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, information is collected through field studies and literature studies to identify student’s needs. Next, at the design stage, media design is carried out to facilitate the production of learning media. The development stage is carried out by realizing the designs that have been designed into interactive video products. The final stage is evaluation, where the media is validated by three material experts and three media experts to assess the suitability of the product. The results of the study indicate that the developed interactive video is highly feasible for use based on validation from experts. The assessment by the media expert resulted in an Aiken index value of 0.8, which falls into the high validity category, while the assessment by the content expert resulted in an Aiken index value of 0.9, which falls into the high validity category.